Microtubule cytoskeleton perturbation induced by taxol and colchicine affects chaperonin containing TCP-1 (CCT) subunit gene expression in Tetrahymena cells - Casalou, Cristina (2018)
We report the existence of a CCTϵ subunit gene that encodes subunit ϵ of the chaperonin CCT (chaperonin containing TCP-1) in Tetrahymena pyriformis. This work focuses on the study of the effects of the microtubule polymerizing agent taxol and the depolymerizing agent colchicine on microtubule dynamics and their role in the regulation of tubulin and CCT subunit genes. Under taxol treatment some TpCCT and tubulin genes are distinctly expressed until 30 min of treatment. Cytoplasmic TpCCT mRNA levels slightly decrease while tubulin transcripts are increasing. In colchicine treated cells TpCCT and tubulin transcripts decrease in the initial 30 min of treatment and then start to increase. However, both antimitotic agents induce TpCCT and tubulin gene transcription. This induction does not correlate with increased steady-state levels of TpCCT proteins and seems to be necessary to replete cytoplasmic TpCCT mRNAs. Moreover, we found that TpCCTϵ and TpCCTα but not TpCCTη are present in the insoluble fraction after a postmitochondrial fractionation that contains components of the ciliate cortex structure, basal bodies and cilia. This suggests that some TpCCT subunits may be associated with these structures. The association of TpCCTϵ subunit is stimulated either by taxol or colchicine treatment. These observations support the idea that CCT subunits could have additional roles in vivo.